Hydatid Cyst of Infratemporal Region - A Rare Case Report - K. Umesh; N.Sulabha A; C. Sameer A; W. Neelakant. M; N.C. Sangamesh; Patel Mohammad Ali R (Al Ameen Medical College, 2010)
Hydatid disease, caused by larval stage of parasite echinococcus, is considerable health problem world wide. Hydatid cyst of infratemporal region is extremely rare, even in endemic areas. A 35 year old woman presented with slowly progressive swelling in infratemporal region. At operation the cystic mass was demonstrated and histopathologic examination confirmed the diagnosis of hydatid cyst. A high index of suspicion is necessary to diagnose the hydatid cyst in an unusual location and in non-endemic areas. When incidence in maxillofacial region is rare, hydatid cyst should be considered in differential diagnosis of benign swellings of orofacial region.